A Review on the Role of Mitochondrial DNA Mutations in Cancer - Dahi, Farzaneh; Mortezanejad, Sahar; Geranpayeh, Loabat; Shahbazi, Shirin (Archives of Medical Laboratory Sciences, 2021)
Mitochondria implement various cellular functions, including energy production through the electron transport chain by oxidative phosphorylation mechanism. These respiratory chains consist of several complexes and protein subunits which are encoded by nuclear and mitochondrial genes. Due to mutation susceptibility and repair limitation, more aberrations have occurred in mitochondrial DNA in comparison to nuclear DNA. Given the fact that mitochondrial DNA lacks introns, mutations almost occur in the coding sequence, which comprises a direct impact on its functions. Emerging evidence indicates that mutations in the mitochondrial DNA led to the production of reactive oxygen species, disrupted apoptosis, and tumor development. Studies reported various somatic and germline variants in mitochondrial DNA related to tumorigenesis. The D-loop region which is the starting point for replication and transcription of mitochondrial DNA is the most prevalent site of somatic mutations in solid tumors. The D-loop mutations also cause copy number variations which are gaining interest in studies of solid tumors including breast cancer, colon cancer, hepatocellular carcinomas, and prostate cancer. Most studies have reported a mitochondrial DNA reduction which subsequently prevents apoptosis and promotes metastasis. The mitochondrial DNA region-specific haplogroups are also involved in the sequence variations due to processes such as genetic drift and adaptive selection. This review article discusses the biology and function of mitochondria and related genes. By explanation of mitochondrial dysfunction caused by different kinds of alterations, we attempt to elucidate the role of mitochondria in tumorigenesis. Prominently published articles in this field were reviewed and the role of germline and somatic mutations of mitochondrial DNA have been investigated in common cancers. *Corresponding Author: Shirin Shahbazi; Email: sh.shahbazi@modares.ac.ir; ORCID iD: 0000-0002-7634-5350 Please cite this article as: Dahi F, Mortezanejad S, Nakhaee S, Geranpayeh L, Shahbazi S. A Review on the Role of Mitochondrial DNA Mutations in Cancer. Arch Med Lab Sci. 2021;7:1-12 (e18). https://doi.org/10.22037/amls.v7.34736